التحكيم وفقًا لاتفاقية الأمم المتحدة بشأن نقل البضائع عن طريق البحر (هامبورغ، 1978) - Ghassan, ali; Haidara, jaber (Tishreen University journal of research and scientific studies -economic and legal sciences, 2024)
International maritime transport represents the backbone of international trade in our current era, for many reasons, such as low costs and the ability to transport large quantities of goods at once. The United Nations Convention on the Maritime Transport of Goods of 1978, known as the Hamburg Convention, represents a qualitative shift in regulating the rules of maritime transport of goods. Among the important topics regulated by the agreement is the subject of arbitration, as it is the most important means of settling disputes related to international trade contracts, especially the contract for the maritime carriage of goods. Accordingly, this research studies the rules of the Hamburg Convention related to arbitration as a means of settling disputes related to the contract for the maritime carriage of goods. يمثل النقل البحري الدولي عصب التجارة الدولية في عصرنا الحالي، ألسباب عديدة كانخفاض التكاليف والقدرة عمى والمعروفة 1978 نقل كميات كبيرة من البضائع دفعة واحدة، وتمثل اتفاقية األمم المتحدة لمنقل البحري لمبضائع لعام ىامبورغ، نقمة نوعية عمى صعيد تنظيم قواعد النقل البحري لمبضائع، ومن بين الموضوعات اليامة التي باسم اتفاقية نظمتيا االتفاقية، موضوع التحكيم، باعتباره أىم وسائل تسوية النزاعات المرتبطة بعقود التجارة الدولية، وخاصة عقد د اتفاقية ىامبورغ المتعمقة بالتحكيم كوسيمة لتسوية النزاعات النقل البحري لمبضائع، وبناء عميو يتناول ىذا البحث قواع ال
Keywords: Arbitration; Bill of lading; Bills of lading; Carriage of Goods by Sea (1978); Hamburg Convention; Hamburg Rules; International commercial arbitration; Maritime carriage contract; Maritime transport; UN Convention; اتفاقية ىامبورغ; التحكيم; سند الشحن; عقد النقل البحري

الأعوان التجاريون لعملية النقل البحري - قزدعلي, أسماء (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص : نظم القانون البحري الجزائري مهام و مسؤوليات كل من وكيل السفينة ووكيل الحمولة في المواد من 609 إلى 630 أما السمسار البحري فمن المادة 631 إلى المادة 639 ، فتعتبر هذه الأنشطة وليدة خوصصة النشاطات البحرية التي كانت محتكرة من قبل الدولة سابقا بالإضافة إلى ما أصبحت عليه السفن التجارية و تكاليفها الباهضة . كان ربان السفينة هو من يتولى القيام بهذه الأنشطة ذلك لحساب المجهز أو المرسل إليه ، فاقتضى الأمر إعفاءه منها ذلك نظرا لبقاء السفينة في الميناء مدة طويلة والبحث عن شخص طبيعي أو معنوي في كل ميناء يقوم لحساب المجهز أو المرسل إليه بتسليم البضائع وحراستها و المحافظة عليها و تحصيل الأجر عن ذلك . وعليه أصبح الأعوان التجاريون هم من يتولون القيام بهذه الأنشطة و المهام وذلك بناءا على عقد تنجر عنه جملة من الالتزامات و المسؤوليات على عاتق طرفاه . Le droit maritime algérien réglemente les fonctions et les responsabilités de consignataire du navire et de consignataire de cargaison dans les articles de 609 à 630. Le courtier naval de l’article 631 à l’article 639 considère ces activités comme la naissance de la privatisation des activités maritimes précédemment monopolisées par l’État en plus de ce que sont devenus les navires commerciaux et leurs coûts exorbitants. C’est le capitaine du navire qui a effectué ces activités au nom du transformateur ou du destinataire. Cela était rendu nécessaire par l’exemption, compte tenu du long séjour du navire au port et de la recherche d’une personne physique ou morale dans chaque port pour lequel le transformateur ou le destinataire livrait, gardait, entretenait et percevait les salaires. En conséquence, ce sont les agents commerciaux qui exercent ces activités et fonctions sur la base d’un contrat qui remplit un certain nombre d’obligations et de responsabilités des deux parties. Algerian maritime law regulates the duties and responsibilities of the ship’s agent and cargo agent in the section from 609 to 630. The naval broker from section 631 to section 639 considers these activities to be the birth of the privatization of maritime activities previously monopolized by the State in addition to what has become of commercial vessels and their exorbitant costs. The master of the vessel performed these activities on behalf of the processor or consignee. This was made necessary by the exemption, taking into account the vessel’s long stay in port and the search for a natural or legal person in each port for which the processor or consignee delivered, kept, maintained and collected wages. Consequently, it is the commercial agents who carry out these activities and functions on the basis of a contract which fulfils a number of obligations and responsibilities of both parties.
Keywords: Agency contract; Consignataire de cargaison; Consignataire de navire; Contrat de transport maritime; Contrat d’agence; Courtier maritime; Droit algérien; Droit maritime; Navire; Payload agent; Sea broker; Sea transport contract; Ship agent

The Role of the Foreign Cause in the Exemption of the Marine Carrier from Liability in accordance with the Rotterdam Rules: A Comparative legal study - Harb, Mohamed (UAEU Law Journal, 2022)

مراكز التحكيم البحري - بلقاسم, حبيب (Université d'Oran 2 Mohamed Ben Ahmed, 2021)
"Les centres d’arbitrage maritime." Résumé : Le sujet des centres d'arbitrage maritime concerne le processus de résolution des contentieux maritimes quand leurs parties optent pour soumettre leur différend à des instances d'arbitrage comme voie alternative. Les centres d'arbitrage maritime appliquent le règlement arbitral et ses règles dans le cas où le choix est fait en fonction de la clause compromissoire qui inclut ce choix ainsi que la loi applicable. Lacompétence de cet instance d'arbitrage convenue débute à la date de la soumission de la demande d'arbitrage, afin de lui confier le suivi des procédures d'arbitrage et de tout ce qui touche au litige arbitral et jusqu' à ce que la sentence (décision) arbitrale soit rendue. "Maritime arbitration centers." Summary: The subject of maritime arbitration centers concerns the process of resolving maritime disputes when their parties opt to submit their dispute to the arbitral tribunal as an alternative solution, and maritime arbitration centers apply arbitration regulations and its rules in case where the choice is made according to the arbitration clause which includes this choice as well as applying the law on all disputes. The arbitral tribunal function starts from the date of submitting the arbitration request to it to be entrusted with following up the arbitration procedures and everything related to the arbitration dispute and until the arbitral award is issued. : الملخص يتعلق موضوع مراكز التحكيم البحري بعملية فض المنازعات البحرية التي يختار أطرافها عرض النزاع على هيئات التحكيم كطريق بديل، و مراكز التحكيم البحري تعمل على تطبيق لوائح التحكيم و نظامها التحكيمي في حال وقوع الاختيار عليها وفقا لشرط التحكيم الذي يتضمن هذا الاختيار، إلى جانب القانون الواجب التطبيق على النزاع. و يبدأ اختصاص هذه الهيئة في التحكيم المؤسسي من تاريخ تقديم طلب التحكيم إليها، ليوكل لها متابعة إجراءات التحكيم و كل ما يتعلق بالمنازعة التحكيمية و إلى غاية صدور الحكم التحكيمي.
Keywords: Application for arbitration; Arbitral Awards; Arbitration; Centres d'arbitrage maritime; Clause d'arbitrage maritime; Demande d'arbitrage; Décision d'arbitrage; Maritime arbitration centres; Maritime arbitration clause